Comparative life cycle energy and greenhouse gas footprints of dry and wet torrefaction processes of various biomass feedstocks. Issue 4 (August 2021) - Akbari, Maryam; Oyedun, Adetoyese Olajire; Gemechu, Eskinder; Kumar, Amit
Abstract: This study compares the life cycle energy consumption and greenhouse gas (GHG) emissions of electricity generation from bio-coals produced from various biomass feedstocks via dry torrefaction (DT) and wet torrefaction (WT) processes. Wheat straw, pine woodchips, grape pomace, manure and algae are the main feedstocks evaluated. The energy consumption and the associated GHG emissions at each life cycle stage were calculated. The main stages included are in-field preparation, feedstocks transportation to torrefaction plant, torrefaction process, bio-coal transportation to power plant, and power plant operations. The results show that all pathways are competitive with coal-based electricity in terms of GHG emissions except pathways with algae as feedstock and manure biochar-based electricity generation. Among the pathways, electricity generation from pine woodchips biochar appears to be the best option, with an 82% GHG emissions reduction compared to coal-derived electricity, followed by wheat starw biochar and grape pomace hydrochar with 80% and 75% emission reductions, respectively. Electricity generation from wheat straw biochar, pine woodchips biochar, and grape pomace hydrochar lead to the highest net energy ratios (NERs) of 4.19, 3.58, and 2.59, respectively. The results also show that the combustion of the biomass for supplying electricity used in the plant decreases GHG emissions in all pathways particularly in WT ones. Sensitivity analysis of using different emissions allocation methods, transportation distances to torrefaction plant and to power plant, emission factor of electricity consumed, and quantity of natural gas consumed were aslo conducted. The developed information is novel and can be used for investment decisions and policy formulation around the world. Graphical Abstract: ga1 Highlights: Electricity production from dry and wet torrefied of various biomasses is studied. The feedstocks include wheat straw, wood chips, grape pomace manure and algae. NER and GHG emissions of the life cycle of electricity generation are evaluated. Pathways' GHG emissions are compared with coal- and NG-based electricity generation.